2016
DOI: 10.3892/etm.2016.3228
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid is associated with increased risk of idiopathic venous thromboembolism in high HDL-C population: A case-control study

Abstract: Many studies have indicated that metabolic disorders are positively correlated with idiopathic venous thromboembolism (VTE), whereas the risk factor serum uric acid (SUA) for idiopathic VTE has yet to be investigated. In this retrospective case-control study, 276 idiopathic VTE patients and 536 gender- and age-matched control subjects were included. The subjects in the case and control groups exhibiting common known VTE risk factors and the patients with a first VTE onset in one month were excluded. For the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…Several cohort studies showed that serum uric acid (SUA) level is an independent risk factor of VTE (42)(43)(44). Though our MR data does not show a significant association between high level with VTE, the p-value is around the border of suggestive significance (p = 0.078) and suggested a trend toward increasing VTE risk.…”
Section: Lipid Profiles and Vtecontrasting
confidence: 81%
“…Several cohort studies showed that serum uric acid (SUA) level is an independent risk factor of VTE (42)(43)(44). Though our MR data does not show a significant association between high level with VTE, the p-value is around the border of suggestive significance (p = 0.078) and suggested a trend toward increasing VTE risk.…”
Section: Lipid Profiles and Vtecontrasting
confidence: 81%
“…In 200 hypertensive patients that have normal treadmill exercise test, patients with erectile dysfunction have significantly higher SUA [182] . In persons with elevated level of HDLc, SUA is associated with an increased risk of idiopathic venous thromboembolism [183] . In patients with hypertrophic cardiomyopathy, SUA is a significant predictor of adverse outcome [184] .…”
Section: Uric Acid and Cardiovascular System (Cvs)mentioning
confidence: 99%
“…1719 Previous studies showed the in vitro role of UA in endothelial dysfunction and it is shown that it could inhibit endothelial release of nitric oxide and block endothelial cell proliferation in vitro. 2022 Uric acid and thrombosis are also being investigated in a variety of recent studies 23 but we could not able to find a study about anterior uveitis and uric acid. Behcet's disease is a syndrome characterized by inflammation, so we examined whether anterior uveal involvement, a part of the inflammatory side of this disease, is directly related to a parameter known to be associated with inflammatory processes such as uric acid.…”
Section: Introductionmentioning
confidence: 89%